NONVERBAL COMMUNICATION IN HOTEL CHECK-IN PROCEDURES THROUGH BIRDWHISTELL’S KINESICS ANALYSIS ON LINGUA TV YOUTUBE VIDEO - Eka Kusumawati; Putu Suarcaya; Ni Putu Era Marsakawati (Undiksha Press, 2026)
This present study examined the use of nonverbal communication in the simulation of check-in process in the hotel published on YouTube by LinguaTV. The purpose of this study is to identify the types of nonverbal communication which are shown by front office staff during the check-in process, utilizing Birdwhistell’s kinesics theory. This study employed a qualitative descriptive design with data collection through repeated observation toward the chosen video that focus on four kinesics aspects, namely facial expression, posture, gesture, and eye contact. The result of this study showed all four nonverbal communication presented in the interaction. However, the frequency level and the function was different. Facial expression and eye contact became the most dominant elements utilized consistently to deliver warm attention and professionalism, while posture, precisely standing upright and leaning forward in specific moments, mirrors readiness and engagement. Additionally, gestures are used selectively to support procedural actions such as providing guidance and handling documents. This current study also found all the non-verbal elements work in accordance as a complete communication system. Thus, it increased the clarity of the message and maintained the quality through interaction. Overall, the result of this study showed that non-verbal communication holds a crucial role in forming effective surface encounters even in a simulated digital context. This study suggested that educational video could serve as valuable resources for learning and analyzing professional communication in the hospitality field.